A metal-free heptazine–porphyrin based porous polymeric network as an artificial leaf for carbon-free solar fuels. Issue 27 (29th June 2022) - Kumar, Sunil; Battula, Venugopala Rao; Sharma, Neha; Samanta, Soumadri; Rawat, Bhawna; Kailasam, Kamalakannan
Abstract : Carbon-free solar fuel production driven by artificial photosynthesis over heptazine–porphyrin-based polymeric network as photocatalyst. Abstract : Carbon-free solar fuel production driven by solar energy has become a holy grail for a future sustainable world. In recent years, much interest has been centered on hydrogen peroxide (H2 O2 ), a carbon-free solar fuel that is superior to hydrogen (H2 ) in terms of transportation and direct use in membrane-free fuel cells. Thus, H2 O2 production using solar energy from pure water over visible-light-active photocatalysts is a more sustainable approach than existing anthraquinone-based processes. Herein, for the first time, a metal-free heptazine-based porous polymeric network (HMP-PPR) featuring heptazine and porphyrin units bridged through –NH– bonds is developed. Under simulated sunlight, HMP-PPR shows nearly 9 times higher H2 O2 production than graphitic carbon nitride (g-CN). Further, HMP-PPR stably generates 750 μmol g −1 H2 O2 over propan-2-ol in 24 h. Interestingly, under natural sunlight, it produces 151 μmol g −1 H2 O2 from pure water in 4 h through both a two-electron oxygen reduction reaction and two-electron water oxidation. Such exciting results are explained based on the unique band positions of the material, oxygraph analysis, and theoretical studies. This study explains the importance of heptazine-based porous polymeric networks in liquid solar fuel production.